2017
DOI: 10.3390/toxins10010019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Oral Adsorbent AST-120 on Organ-Specific Accumulation of Uremic Toxins: LC-MS/MS and MS Imaging Techniques

Abstract: Elevated circulating uremic toxins are associated with a variety of symptoms and organ dysfunction observed in patients with chronic kidney disease (CKD). Indoxyl sulfate (IS) and p-cresyl sulfate (PCS) are representative uremic toxins that exert various harmful effects. We recently showed that IS induces metabolic alteration in skeletal muscle and causes sarcopenia in mice. However, whether organ-specific accumulation of IS and PCS is associated with tissue dysfunction is still unclear. We investigated the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 52 publications
2
60
1
1
Order By: Relevance
“…However, the beneficial of AST-120 is still controversial. In a renal failure mouse model induced by adenine, AST-120 did not show an improvement in renal function and fibrosis despite a significant reduction in IS and pCS accumulation in the renal tissue [ 207 ]. Large scale randomized controlled trials in moderate to severe CKD (pre-dialysis) patients failed to show renal benefits of AST-120 on the delay in CKD progression despite a significantly better preservation of renal function in AST-120 treated than placebo groups [ 208 , 209 ].…”
Section: Cardiac Effects Of Protein-bound Moleculesmentioning
confidence: 99%
“…However, the beneficial of AST-120 is still controversial. In a renal failure mouse model induced by adenine, AST-120 did not show an improvement in renal function and fibrosis despite a significant reduction in IS and pCS accumulation in the renal tissue [ 207 ]. Large scale randomized controlled trials in moderate to severe CKD (pre-dialysis) patients failed to show renal benefits of AST-120 on the delay in CKD progression despite a significantly better preservation of renal function in AST-120 treated than placebo groups [ 208 , 209 ].…”
Section: Cardiac Effects Of Protein-bound Moleculesmentioning
confidence: 99%
“…AST-120 is an oral carbonic adsorbent which is used to decrease the absorption of uremic toxins, such as indols and retard CKD in Japan [ 121 ]. In experimental CKD, it reduces tissue accumulation of IS and pCS in diverse tissues, including the kidney and protected the kidneys in several animal models of AKI and CKD [ 122 ], However, two large multinational trials (EPPIC-1 and EPPIC-2), failed to show benefit on CKD progression [ 123 ]. However, a post-hoc, hypothesis-generating analysis observed that in the subgroup of high risk patients (urinary creatinine ratio ≥1.0 and haematuria) who were additionally treated with renin-angiotensin system blockade, AST-120 may have provided additional benefit in retarding CKD progression [ 124 ].…”
Section: Nephroprotection Interventional Studies Targeting the Intmentioning
confidence: 99%
“…AST-120, a kind of absorbent, has been reported to absorb indole in the gut, thus, decreasing the amount of absorbed indole leading to decreased IS concentrations and delayed CKD progression. 27 , 28 These reports have proven that decreasing gut indole production may be an attractive and promising strategy for delaying CKD progression. However, modulation of the gut microbial metabolic pathway and indole production by small molecules has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%